EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN CONCEPT MAPPING PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VIII SMP SE-KABUPATEN KEBUMEN TAHUN PELAJARAN 2015/2016 - Sasongko, Anggi; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this research was to determine the effect of the learning models TSTS with Concept Mapping (TSTS CM) on mathematics learning achievement viewed from students Mathematical Reasoning Ability (MRA). This research was quasi experimental research with 3x3 factorial design. The population were the eighth-grade students of junior high schools in Kebumen Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and MRA test. The data analysis technique used was the two-way ANAVA with unbalanced cell. Based on the hypothesis test, it was concluded as follows. 1) The mathematics learning achievement of the students who were treated by TSTS CM was better than the students who were treated by TSTS and Direct Learning (DL), the mathematics learning achievement of the students who were treated by TSTS was better than the students who were treated by DL; 2) The mathematics learning achievement of the students with high MRA was better than the students with moderate or low MRA, and the mathematics learning achievement of the students with moderate MRA was better than the students with low MRA; 3) In TSTS CM, the mathematics learning achievement of the students who had high MRA was better than the students who had moderate or low MRA, while the mathematics learning achievement of the students who had moderate MRA was same as the students who had low MRA; in TSTS, the mathematics learning achievement of the students who hadÂ  high MRA was same as the students who had moderate MRA and was better than the students who had low MRA, while the mathematics learning achievement of the student who had moderate MRA was better than the students who had low MRA; in DL, the mathematics learning achievement of the students who had high MRA was better than the students who had moderate or low MRA, while the mathematics learning achievement of the students who had moderate MRA was same as the students who had low MRA; 4) The high MRA students who were treated by TSTS CM, TSTS, and DL had same mathematics learning achievement; the moderate MRA students who were treated by TSTS CM had same mathematics learning achievement as the students were treated by TSTS but had better than the students were treated by DL, while the students were treated by TSTS had better mathematics learning achievement than the students were treated by DL; The low MRA students who were treated by TSTS CM had better mathematics learning achievement than the students were treated by TSTS or DL, while the students were treated by TSTS had same mathematics learning achievement as the students were treated by DL.Keywords: Two Stay Two Stray, Concept Mapping, Direct Learning, Mathematical Reasoning Ability